Ten year recurrence after first ever stroke in a Japanese community: the Hisayama study. Issue 3 (16th February 2005) - Hata, J; Tanizaki, Y; Kiyohara, Y; Kato, I; Kubo, M; Tanaka, K; Okubo, K; Nakamura, H; Oishi, Y; Ibayashi, S; Iida, M
Abstract : Background: Very few population based cohort studies have focused on the long term recurrence of stroke. Objective: To examine 10 year cumulative recurrence rates for stroke in a Japanese cohort according to pathological type and clinical subtype of brain infarction. Methods: During a 32 year follow up of 1621 subjects ⩾40 years of age, 410 developed first ever stroke. These were followed up prospectively for 10 years after stroke onset. Results: During follow up, 108 (26%) experienced recurrent stroke. The cumulative recurrence rates were 35.3% at five years and 51.3% at 10 years. The 10 year recurrence rates of subarachnoid haemorrhage (SAH), brain haemorrhage, and brain infarction were 70.0%, 55.6%, and 49.7%, respectively; the difference between SAH and brain infarction was significant (p = 0.004). Most recurrent episodes after SAH or brain haemorrhage happened within a year after the index stroke, whereas recurrence of brain infarction increased consistently throughout the observation period. Cardioembolic stroke had a higher recurrence rate (75.2%) than lacunar infarction (46.8%) (p = 0.049). The 10 year risk of stroke recurrence increased with age after lacunar or atherothrombotic brain infarction, but not after the other types or subtypes. After atherothrombotic brain infarction, cardioembolic stroke, or SAH, the type and subtype of most recurrent strokes were the same as for the index stroke, but recurrence after lacunar infarction or brain haemorrhage showed divergent patterns. Conclusions: Japanese people have higher recurrence rates of stroke than other populations. Recurrence rate after a first brain infarct increases consistently through the next 10 years.